2016
DOI: 10.18203/2320-1770.ijrcog20161668
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study of rate, indications and complications of primary caesarean section

Abstract: Background:The indications for cesarean sections have been undergoing a gradual change over the last few decades. Besides the obstetric causes, several other medical, social, ethical, economic and medico legal factors play a role in this rising trend of cesarean section. Initially it was performed mainly for maternal interest but recently the health of the fetus has played a significant role in making the decision for a cesarean birth. This study was conducted to determine the rate, indications and complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 0 publications
4
17
0
Order By: Relevance
“…15 Mean age of our study participants was 12.16 years with maximum (36.5%) patient between 26-30 year age group, which was comparable with other studies, in our study 183 (39%) patients were nulliparous, primary cesarean rate was quite high (88.8%) in our study then earlier studies. 2,13 Fetal distress was the commonest indication (25.1%) of LSCS in our study, followed by previous cesarean section (22.2%). Among preexisting obstetric indications hypertensive disorders of pregnancy contributed to LSCS in 87 (18.3%) patients, 39 (8.2%) had ante partum eclampsia.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…15 Mean age of our study participants was 12.16 years with maximum (36.5%) patient between 26-30 year age group, which was comparable with other studies, in our study 183 (39%) patients were nulliparous, primary cesarean rate was quite high (88.8%) in our study then earlier studies. 2,13 Fetal distress was the commonest indication (25.1%) of LSCS in our study, followed by previous cesarean section (22.2%). Among preexisting obstetric indications hypertensive disorders of pregnancy contributed to LSCS in 87 (18.3%) patients, 39 (8.2%) had ante partum eclampsia.…”
Section: Discussionmentioning
confidence: 58%
“…Our results are similar to earlier reports from other medical colleges of India on the contrary Daniel S et al reported higher incidence (total 28.7%) elective 46.06% and 53.9%) although the observed incidence in our study is far lower than reported from sub-Saharan countries. 2,11,13,14 In Asia survey the overall cesarean rate was 27.3%. China had the highest overall cesarean rates (46.2%) followed by Vietnam, Thailand and Sri Lanka; Cambodia had the lower (14.7%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially it was preferred for maternal interest but nowadays foetal health has also played a significant role. 6 CS may be associated with short term and long term risks. Short term maternal risks associated with a CS includes bleeding, injury to the urogenital or gastrointestinal organs, post-operative infection and risks for deep vein thrombosis.…”
Section: Introductionmentioning
confidence: 99%